Histone acetyltransferase HAM1 interacts with molecular chaperone DNAJA2 and confers immune responses through salicylic acid biosynthetic genes in cassava. (8th December 2022) - Zhao, Huiping; Ge, Zhongyuan; Zhou, Mengmeng; Bai, Ruoyu; Zeng, Hongqiu; Wei, Yunxie; He, Chaozu; Shi, Haitao
Abstract: Cassava bacterial blight (CBB) is one of the most serious diseases in cassava production, so it is essential to explore the underlying mechanism of immune responses. Histone acetylation is an important epigenetic modification, however, its relationship with cassava disease resistance remains unclear. Here, we identified 10 histone acetyltransferases in cassava and found that the transcript of MeHAM1 showed the highest induction to CBB. Functional analysis showed that MeHAM1 positively regulated disease resistance to CBB through modulation of salicylic acid (SA) accumulation. Further investigation revealed that MeHAM1 directly activated SA biosynthetic genes' expression via promoting lysine 9 of histone 3 (H3K9) acetylation and lysine 5 of histone 4 (H4K5) acetylation of these genes. In addition, molecular chaperone MeDNAJA2 physically interacted with MeHAM1, and MeDNAJA2 also regulated plant immune responses and SA biosynthetic genes. In conclusion, this study illustrates that MeHAM1 and MeDNAJA2 confer immune responses through transcriptional programming of SA biosynthetic genes via histone acetylation. The MeHAM1 & MeDNAJA2‐SA biosynthesis module not only constructs the direct relationship between histone acetylation and cassava disease resistance, but also provides gene network with potential value for genetic improvement of cassava disease resistance. Summary statement: Histone acetyltransferase MeHAM1 interacts with molecular chaperone MeDNAJA2, and both of them confer immune responses through promoting histone acetylation of SA biosynthetic genes and SA accumulation.